Nisarg Nirman: the social farming venture from India. Issue 8 (26th November 2015) - Sohoni, Vandana; Joshi, Anjali
Abstract : Subject area: Entrepreneurship, Business Strategy. Study level/applicability: The case is designed for business students at the undergraduate or MBA levels in courses that deal with social entrepreneurship. The case describes the future growth potential of the exotic vegetable/fruit market in emerging economy India and lends itself for use in Rural Management courses as well. Case overview: Nisarg Nirman Agro Products Private Limited (hereafter referred as NNPL), a social farming venture, was started by Anjali Churi in the year 1997 in India. Churi, an agriculturist at heart, was always interested in experimenting and conducting research on new crops. What started as a small research experiment soon prospered to become a commercial venture producing and selling exotic vegetables to the Indian business customers, such as the five-/four-star hotels, premier clubs, hypermarkets, etc. NNPL was one among the pioneers to start the cultivation of exotic vegetables in the country. Their indigenous produce was of high quality. Their business customers were benefitted by the freshness of their products as well as competitive pricing as compared to their earlier imports. In her journey to commercial prosperity, she adopted co-operative farming, thus providing employment and livelihood opportunities to Indian farmers. Over the period, NNPL was invited to provide agriculture consulting to some of the other countries, such as Maldives, Thailand and Israel. In 2014, the company boasted of an indigenous produce of 95 different varieties of exotic vegetables and fruits, with 34 clients across the country, revenues to the tune of INR40 million and touching lives of more than 600 farmers across the country. The Indian exotic vegetables market had a promising future. Churi desired to expand her venture but in a manner that could systematically impact and generate employment opportunities for the rural Indians. She was at crossroads to deciding what could be such a venture, agro-processing or agro-tourism? Any such expansions required substantial investments for agricultural research activities. The case is structured to achieve the following pedagogical objectives: a social entrepreneur's ability to identify and exploit the market opportunity for growing own venture as well as generating a larger social impact; understand the industry's change trajectory and its impact on the venture; understand the importance of such business models of cooperative farming in populous emerging economies such as India where 70 per cent of the population resides in rural India. Expected learning outcomes: The case that maps the growth/challenges of a social farming venture and allows students to: understand that small social venture also has the ability to generate a larger social impact; evaluate the venture's strategic positioning and scope in a competitive environment; and evaluate the need and potential of business models as cooperative farming to generate employment at the base of the pyramid in populous emerging economy as India. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.